Pemberdayaan Melalui Edukasi Demonstrasi Video Terhadap Kemampuan Pertolongan Pertama Tersedak Pada PMR Di MAN 3 Kediri - Girianto, Pria Wahyu Romadhon (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2024)
Choking can be experienced by all age groups. Choking was the fourth-leading cause of unintentional death. As a result of choking conditions, a person will experience disruption or blockage of the respiratory tract. Adolescents, in their daily activities, are prone to choking due to food purchased at school. Empowerment through video demonstration education on choking first aid skills in PMR at MAN 3 Kediri aimed to determine the ability of cadres and members to perform choking first aid with a population of 40 students and a sample of 20 students with 5 cadres and 15 cadre members. This service instrument uses an observation sheet. The results of the evaluation of cadres and members before being given the intervention show that most (65%) of the respondents had abilities in the less category, with a 46.25 (less). After being given the intervention, most respondents (55%) could first aid choking in the good category. mean 84.35 (good) means that there is an increase in the ability of first aid choking in PMR members MAN 3 Kediri. This shows that with educational methods and demonstration videos, there is an increase in the ability to provide first aid for choking in PMR cadres and cadre members at MAN 3 Kediri because, with these methods, the delivery of material is more interesting and can increase cadre understanding. First aid for choking should be given to all school and community members to prevent choking.